Analyzing SHORE A hardness to assess the durability of soft denture lining materials - Gonçalves, Natália Inês; Pierre, Fernanda Zapater; Borges , Alexandre Luiz Souto; Silva, João Maurício Ferraz da; Uemura, Eduardo Shigueyuki (Brazilian Dental Science, 2023)
Objective: Evaluate the “SHORE A” hardness in four denture soft lining materials at different time intervals. Material and Methods: Forty disc-shaped specimens, with dimensions of 15 mm × 3 mm, were distributed into four groups according to the materials: SC (Soft Confort); TS (Trusoft); UG (Ufi Gel P) and DS (Dentusoft) (n=10). The hardness measurements were performed using a portable digital hardness meter at 1 hour (h), 3 days (d), 7 d, 15 d, 30 and 60 d after preparation of specimens. The data were subjected to statistical analysis. Results: UG presented the highest hardness (39,09±2,27), followed by SC (34,36±8,52), DS (26,23±5,26) and finally TS (18,05±3,60), being that UG and TS had the smaller change in hardness between time intervals. The Repeated Measures ANOVA and Tukey’s test showed that the variables (material and time) and their interaction had differences statistically significant (p